Exploring the Linguistic Landscape of a Heritage Town in the island province of Marinduque, Philippines - Luna, Cherie Ann (International Journal of Arts, Sciences and Education, 2023)
Linguistic landscape studies provide a lens with which the diversity of languages in a sociolinguistic setting can be seen. Through LL, one can see the language preferences in an area and the domains or locations occupied by such languages. This study intends to explore the linguistic landscape in the Boac población, the capital town of Marinduque province, and identify the description of its LL and the present language preferences. Employing Ben-Rafael’s (2006) classification of top-down and bottom-up signs, and Barni and Bagna’s (2009) semiotic analysis using the location and domain variables, this study examines the language preference of government agencies and private business establishments that are used in the signs they place in población along with its significance in the locations and domains where they are placed. The findings show that English is the dominant language in Boac población which is primarily because the location is commercial in nature and the seat of government, therefore English occupies the domains of commerce and institutional control with key sectors of economy and civil administration. Filipino is also seen in permanent commemorative signs which are placed in strategic location in the plaza occupying the domain of locals and even visitors’ cultural activities. Marinduque Tagalog, on the other hand, has a very minimal occurrence in the signs and the positioning of these minimal signs are not even central in the heart of the población which implies a dearth in the attempts to cultivate the use of Marinduque Tagalog in such ways like this.